Strengthening leadership integrity in religious educational institutions; the phenomenon of muhammadiyah boarding schools in Indonesia - Umar, Umar; Setyosari, Punaji; Kamdi, Waras (Universitas Ahmad Dahlan, 2025)
Integrity is a key determinant of effective leadership. Indonesia’s next generation faces various challenges related to integrity and leadership as the country moves toward Indonesia Emas 2045. Strengthening leadership integrity in Islamic boarding schools is unique, as it is rooted in Islamic values. This study describes a model for fostering leadership integrity among future national leaders at Mu’allimin Muhammadiyah Yogyakarta Islamic Boarding School. The research employs a qualitative phenomenological approach. The study involved 17 informants, including kiai, ustaz, community leaders, alumni, musyrif, and students. Researchers actively participated in data collection, which included steps of data reduction, display, and verification. The findings reveal that strengthening the integrity of prospective leaders encompasses several aspects: long-term cadre education policies (for leaders, community, nation), behavior, and open-mindedness (Islamic and national worldview), all developed through value internalization, social interaction, and self-reflection. The balanced development of competencies includes spiritual, intellectual, practical, and moral dimensions. Continuous learning and integration are key features of cadre training at all stages of adolescence. This research contributes to Islamic boarding schools by providing a model for designing and developing leadership integrity systems aligned with Islamic leadership principles. It also highlights the growing public trust in boarding schools as centers for cultivating future leaders’ integrity based on Islamic education. Furthermore, the findings suggest that educational institutions outside the boarding school context can also enhance integrity when guided by a shared vision.